IL-1RI deficiency ameliorates early experimental renal interstitial fibrosis. - Jones, L; O'Sullivan, K; Semple, T; Kuligowski, M; Fukami, K; Ma, F; Nikolic-Paterson, D; Holdsworth, SR; Kitching, A (2009)
BACKGROUND: IL-1beta has the potential to promote progressive renal disease by effects on macrophage recruitment and activation or by effects mediated through tubular cell transforming growth factor (TGF)-beta production, previously demonstrated in vitro. METHODS: The in vivo roles of endogenous IL-1beta and its type I receptor (IL-1RI) in renal fibrosis were studied using wild-type C57BL/6 mice, IL-1beta(-/-) and IL-1RI(-/-) mice with unilateral ureteric obstruction. RESULTS: After 7 days, IL-1RI(-/-) mice (IL-1alpha and IL-1beta deficient) were protected from injury and collagen accumulation. IL-1beta(-/-) mice demonstrated some histological protection, but no reduction in alpha1(1) procollagen mRNA or biochemically measured collagen accumulation. Compared with obstructed kidneys from wild-type mice, TGF-beta1 mRNA was reduced in IL-1RI(-/-) mice (with trends to reduced TGF-beta2 and TGF-beta3). Expression of a downstream TGF-beta effector, connective tissue growth factor, was decreased in IL-1RI(-/-) mice. IL-1RI(-/-) mice exhibited less tubulointerstitial apoptosis compared with wild-type mice. Macrophage infiltration and adhesion molecule mRNA expression was unchanged in IL-1beta(-/-) or IL-1RI(-/-) mice. While TNF expression was similar to wild-type mice, IFN-gamma expression was reduced in both IL-1beta(-/-) and IL-1RI(-/-) mice. IL-1RI(-/-) mice at 14 days showed a catch-up in fibrosis compared with wild-type mice. CONCLUSION: IL-1/IL-1RI interactions are profibrotic in renal fibrosis. IL-1RI(-/-) mice were more protected at an early stage, associated with changes in TGF-beta and downstream mediators of fibrosis, but independent of the presence of infiltrating macrophages.